Penerapan Balanced Scorecard Sebagai Alat Pengukuran Kinerja Umkm Di Indonesia: Studi Literatur Sistematis - Chesya Aletta Delisty; Margareta Dewi Widiarti; Tarissa Budi Syakira; Putri Mutira (CV. ITTC INDONESIA, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in Indonesia’s economy due to their substantial contribution to gross domestic product and employment absorption. However, most MSMEs still rely on simple performance measurement systems that focus primarily on financial aspects. This condition limits business evaluation and reduces the ability to adapt to market changes. The Balanced Scorecard (BSC) is proposed as a comprehensive performance measurement system through four perspectives: financial, customer, internal business processes, and learning and growth. This study aims to analyze the application of the Balanced Scorecard as a performance measurement tool for MSMEs in Indonesia. The research method uses a descriptive qualitative approach through a literature review of relevant national and international scholarly articles. The results indicate that the Balanced Scorecard is able to provide a more holistic, structured, and balanced overview of performance by integrating financial and nonfinancial indicators. The implementation of BSC has been shown to improve financial efficiency, customer satisfaction, and the effectiveness of internal business processes. Nevertheless, the learning and growth perspective remains the main weakness due to limitations in human resource quality, low training intensity, and minimal use of technology. Overall, the Balanced Scorecard is considered relevant, flexible, and adaptive for implementation in MSMEs with adjustments to internal capacity and business conditions. The application of the Balanced Scorecard is expected to support improvements in performance, competitiveness, and the long-term sustainability of MSMEs in Indonesia. This framework strengthens strategic control and supports sustainable decision making aligned with dynamic MSME business environments nationally.